Răspunsuri

2014-10-20T15:58:45+03:00
A) xy+xz=x(y+z)=5*12=60 b) xy+xz-59= x(y+z)=12*5=60c)9y+9z-10x=9(y+z)-10x=9*12-10*5=108-50=58 d) 15y+15z-30= 15(y+z)-30=15*12-30=150e)10xy+2013+10xz=10x(y+z)+2013=10*5*12+2013=600+2013=2613
2014-10-20T15:59:57+03:00
B) xy + xz = x( y+z ) = 5 * 12 = 60
60 - 59 = 1

c) 9y + 9z = 9(y+z) = 108 (1)
10x = 50 (2)
din (1) si (2) => 108 - 50 = 58

d) 15y + 15z = 15( x+y ) = 180
30*x = 30 * 5 = 150
din ele => 180 - 150 = 30

e) 10xy + 10xz (adunarea este comutativa) => 10x(y+z) = 10 * 5 * 12 = 600
600 + 2013 = 2613

Bafta!
1 5 1